DLGAP5 knockdown inactivates the Wnt/β‐catenin signal to repress endometrial cancer cell malignant activities. Issue 3 (1st December 2022) - Chen, Ruipu; Liu, Jing; Hu, Jun; Li, Chunxia; Liu, Yanhua; Pan, Weiwei
Abstract: Human discs large‐associated protein 5 (DLGAP5), a microtubule‐associated protein, has been reported to be upregulated in several tumors. However, the role of DLGAP5 in endometrial cancer (EC) progression and the related underlying mechanism were still unknown. A bioinformatics analysis was performed to analyze the expression and prognostic significance of DLGAP5 in EC tissues using TCGA, CPTAC, Human Protein Atlas, and GSE63678 databases, UALCAN web tool, and the Kaplan–Meier plotter. Effects of DLGAP on EC cell malignant properties were evaluated by CCK‐8, flow cytometry analysis, TUNEL assay, caspase‐3 activity assay, and Transwell invasion assay. The expression of DLGAP5, Wnt3, c‐Myc, Ki67, and cleaved caspase‐3 was detected by western blot analysis. DLGAP5 was highly expressed and correlated with poor prognosis in EC patients. DLGAP5 knockdown inhibited proliferation and invasion, triggered apoptosis, and increased caspase‐3 activity in EC cells. Additionally, DLGAP5 knockdown inactivated the Wnt/β‐catenin signaling pathway in EC cells. Moreover, β‐catenin overexpression abolished the effects of DLGAP5 knockdown on the malignant phenotypes of EC cells. DLGAP5 silencing suppressed the malignant properties in EC cells by inactivating the Wnt/β‐catenin pathway.